PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN PADA PT INFRACOM TECHNOLOGY, JAKARTA PUSAT - Khansa Ainaya Alfatihah; Asep Suherman (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. This study aims to determine the partial and simultaneous effects of Organisational Culture (X1) and Work Environment (X2) on Employee Productivity (Y) at PT InfraCom Technology in Central Jakarta. The method used is quantitative. The object of this study is the employees of PT Infracom Technology in Central Jakarta. The sample in this study consisted of 95 employees. The data analysis and testing techniques included validity and reliability tests, classical tests, simple and multiple linear regression tests, correlation coefficient tests, coefficient of determination tests, and hypothesis testing using Statistical Package for the Science (SPSS) Version 26. The results of this study show that organisational culture partially has a positive effect on employee productivity, as evidenced by the hypothesis test results, which show that the t-count from the organisational culture variable is 4.429, greater than the t-table value of 1.986 with a significance level of 0.000, which is less than 0.05. The work environment partially has a positive effect on employee productivity, as evidenced by the hypothesis test results obtained from the work environment variable, where the t-value is 4.223, which is greater than the t-table value of 1.986 with a significance level of 0.000, which is less than 0.05. Organisational Culture and Work Environment simultaneously have a positive and significant effect on Employee Productivity, as evidenced by the hypothesis test results showing that the calculated f value is greater than the table f value (14.517 > 3) and significance < 0.05 (0.000 < 0.05). This means that it can be concluded that there is a positive and significant simultaneous effect between organisational culture and work environment variables on employee productivity.